Minimal residual disease assessed with deep sequencing of NPM1 mutations predicts relapse after allogeneic stem cell transplant in AML. Issue 2 (28th January 2019) - Delsing Malmberg, Erik; Johansson Alm, Sofie; Nicklasson, Malin; Lazarevic, Vladimir; Ståhlman, Sara; Samuelsson, Tore; Lenhoff, Stig; Asp, Julia; Ehinger, Mats; Palmqvist, Lars; Brune, Mats; Fogelstrand, Linda
Abstract: Mutations in NPM1 can be used for minimal residual disease (MRD) analysis in acute myeloid leukemia (AML). We here applied a newly introduced method, deep sequencing, allowing for simultaneous analysis of all recurrent NPM1 insertions and thus constituting an attractive alternative to multiple PCRs for the clinical laboratory. We retrospectively used deep sequencing for measurement of MRD pre- and post-allogeneic hematopoietic stem cell transplantation (alloHCT). For 29 patients in morphological remission at the time of alloHCT, the effect of deep sequencing MRD on outcome was assessed. MRD positivity was defined as variant allele frequency ≥0.02%. Post-transplant MRD status was significantly and independently associated with clinical outcome; 3-year relapse-free survival 20% vs 85% ( p  < .001), HR 45 (95% CI 2–1260), and overall survival 20% vs 89% ( p  < .001), HR 49 (95% CI 2–1253). Thus, the new methodology deep sequencing is an applicable and predictive tool for MRD assessment in AML.